Training of Mid-Level Specialists in the Telecommunications Area Based on a Trusted Technical Solution - Elena Smirnova; Vladimir Shibanov; Pavel Romasevich (Современные информационные технологии и IT-образование)
The current situation in the world, characterized by sanctions pressure, disruption of logistics, trade, industrial and technological connections and the deepening digitalization of society, has led to a change in the state’s strategy towards the need to quickly reduce technological dependence on foreign manufacturers and transfer the country’s telecommunications infrastructure to trusted domestic solutions. At the same time, at an accelerated pace, it is necessary to develop a system for training senior and mid-level personnel capable of thinking in the paradigm of using exclusively domestic solutions in the design and modernization of the telecommunications component of critical information infrastructure subjects. An example of this approach is the Rosatom Laboratory for Data Communication Networks at the College of the Sirius University of Science and Technology. There, equipment from the T-COM company, part of the Fuel Division of the State Corporation, is available to students. The D-Link Trade company, a Russian legal entity of D-Link Corporation, is a technological partner of T-COM, including D-Link Trade specialists who have developed software for switches included in the Unified Register of Russian Radio-Electronic Products. At the same time, based on the extensive experience in the educational activities of D Link Trade specialists, the T-COM company decided to create a training course “Data transmission and switching in computer networks” together with its technology partner, to support the educational process in Rosatom laboratory at Sirius University College. The content of the course reflects the current state of the telecommunications industry and allows you to train mid-level IT specialists in the design, modernization and operation of multi-service telecommunication networks of various scales and complexity based on domestic equipment - switches of the TGK-125-24/4d-M/T model. The problems of training software developers for telecommunications equipment and the corresponding solutions of the D-Link Trade company in the field of training are considered.